2022
DOI: 10.1111/jce.15489
|View full text |Cite
|
Sign up to set email alerts
|

Early repolarization syndrome, epilepsy, and atrial fibrillation in a young girl with novel KCND3 mutation managed with quinidine

Abstract: A 6‐year‐old girl presented with a difficult to control epilepsy syndrome. On evaluation, additional presyncope episodes associated with polymorphic ventricular tachycardia were also noted. A diagnosis of early repolarization syndrome (ERS) was made with an early repolarization pattern on electrocardiogram, documented VT episodes, and clinical presyncope (proposed Shanghai score 7). Paroxysmal atrial fibrillation (AF) was also noted on 24‐h Holter recordings. The child was stabilized with isoprenaline infusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Though cardiocerebral channelopathy associated with ERS is quite uncommon [ 6 ], few cases have been reported that describe this association where KCND3 mutation is found to be responsible for these phenomena [ 3 , 6 , 8 , 10 , 11 , 13 , 14 ]. The ECG of an 11-year-old girl showed ERP; she was known to have febrile seizures since age two and intellectual disability was found at age six [ 6 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Though cardiocerebral channelopathy associated with ERS is quite uncommon [ 6 ], few cases have been reported that describe this association where KCND3 mutation is found to be responsible for these phenomena [ 3 , 6 , 8 , 10 , 11 , 13 , 14 ]. The ECG of an 11-year-old girl showed ERP; she was known to have febrile seizures since age two and intellectual disability was found at age six [ 6 ].…”
Section: Reviewmentioning
confidence: 99%
“…ERS was found to be linked with epilepsy and intellectual disability in another reported case of a teenage girl, whose sudden death at 16 led to the diagnosis of ERS, a de novo KCND3 V392I mutation was found in her mother, this mutation was also found in her 19-year-old sister who was found to be suffering from ERS as well [ 3 ]. ERS associated with epilepsy and AF has been reported in another six-year-old patient who was found to have a missense mutation in the KCND3 gene [ 13 ], making the association between cardiocerebral channelopathy and ERS evident in these individuals. Takayama et al illustrated a de novo KCND3 Gly306Ala (c.917g>c) heterozygous mutation in a 12-year-old boy whose ECG shows elevation of J points in multiple leads [ 8 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation